2023
DOI: 10.1039/d3ay01400b
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and sensitive colorimetric sensor for hypochlorite detection based on polyvinylpyrrolidone-stabilized gold nanoparticles

Yingjie Ye,
Qian Zhang,
Yongxing Zhang
et al.

Abstract: It is important to develop simple and effective techniques for hypochlorite (OCl–) detection at trace levels due to its widespread use as a disinfectant especially for water treatments including drinking...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…This interaction causes the AuNPs to aggregate, resulting in changes to the absorption spectrum. 48 The shift in the absorption peak from 525 nm to 530 nm is due to the increase in proximity and interaction amongst the AuNPs (Fig. 3B).…”
Section: Resultsmentioning
confidence: 96%
“…This interaction causes the AuNPs to aggregate, resulting in changes to the absorption spectrum. 48 The shift in the absorption peak from 525 nm to 530 nm is due to the increase in proximity and interaction amongst the AuNPs (Fig. 3B).…”
Section: Resultsmentioning
confidence: 96%
“…The aggregation of CuNCs after the introduction of Al 3+ ions indicated that the possible mechanism of fluorescence enhancement was caused by AIE that increases fluorescence intensity and prolongs luminescence lifetime. 62,63 The fluorescence enhancement mechanism of Al 3+ ions on NAC-CuNCs was further studied. The average fluorescence lifetime of CuNCs was increased from 0.79 to 3.80 μs after the addition of Al 3+ ions (Figure 5C).…”
Section: Detection Of Al 3+ By Nac-cunc Probesmentioning
confidence: 99%